MicroRNA-7 Deficiency Ameliorates the Pathologies of Acute Lung Injury through Elevating KLF4 - Zhao, Juanjuan; Chen, Chao; Guo, Mengmeng; Tao, Yijin; Cui, PanPan; Zhou, Ya; Qin, Nalin; Zheng, Jing; Zhang, Jidong; Xu, Lin (Frontiers in Immunology, 2016)
Recent evidence showed that microRNA-7 (miR-7) played an important role in the pathologies of lung-related diseases. However, the potential role of miR-7 in acute lung injury (ALI) still remains poorly understood. Here we assessed the effect of miR-7 deficiency on the pathology of ALI. We firstly found that the expression of miR-7 was upregulated in lung tissue in murine LPS-induced ALI model. Notably, we generated miR-7 knock down (KD) mice by using miRNA-Sponge technique and found that miR-7 deficiency could ameliorate the pathologies of lung as evidenced by accelerated body weight recovery, reduced level of bronchoalveolar lavage (BAL) proinflammatory cytokines and decreased number of BAL cells in ALI mice. Moreover, the proportion and number of various immune cells in BAL, including innate immune cell F4/80+macrophages, γδT cells, NK1.1+T cells and CD11c+DCs, as well as adaptive immune cell CD4+T cells and CD8+T cells, also significantly changed respectively. Mechanistic evidence showed that KLF4, a target molecule of miR-7, was upregulated in lung tissues in ALI model, accompanied by altered transduction of NF-κB, AKT and ERK pathway. These data provided a previously unknown role of miR-7 in pathology of ALI, which could ultimately aid the understanding of development of ALI and the development of new therapeutic strategies against clinical inflammatory lung diseases.